Why Physicians Don't Ask: Interpersonal and Intrapersonal Barriers to HIV Testing—Making a Case for a Patient-Initiated Campaign. (July 2016) - Arya, Monisha; Patel, Sajani; Kumar, Disha; Zheng, Micha Yin; Kallen, Michael A.; Street, Richard L.; Viswanath, Kasisomayajula; Giordano, Thomas P.
In 2006, the US Centers for Disease Control and Prevention recommended HIV testing for all adolescents and adults aged 13 to 64 in health care settings with a HIV prevalence of at least 0.1%. However, 55% of US adults have never been tested and therefore do not know their HIV status. To understand suboptimal HIV testing rates, this study sought to illuminate interpersonal and intrapersonal physician barriers to HIV testing. One hundred and eighty physicians from health centers in Houston completed a survey based on Cabana's Knowledge, Attitudes and Behaviors model. One-third of the physicians faced at least 1 interpersonal barrier to HIV testing, such as a difference in age or language. Many (41%) physicians faced at least 1 intrapersonal barrier, such as believing their patients would be feeling uncomfortable discussing HIV. Notably, 71% of physicians would prefer their patients ask for the test. A patient-engaging campaign may be an innovative solution to increasing HIV testing and reducing the number of undiagnosed persons.